Diagnóstico sectorial de las actividades de peluquería y otros tratamientos de belleza del cantón Loja. - Carrión Cuenca, Gabriela Nataly (2024)
The sectoral diagnosis is a very important tool to evaluate and analyse a specific sector, it provides a detailed study of the key factors of the organisations, for the correct decision making in order to improve the economic growth of a particular sector. The objective of the research is to carry out a sectoral diagnosis of hairdressing and other beauty treatment activities in the Loja canton, in order to achieve a clear vision of the current state of the organisations, with the aim of providing recommendations and strategies to improve the competitiveness of the sector, through innovation in services, continuous improvement and the variety and quality of the products used. The methodology used was mixed, with a descriptive, exploratory and field research type, the main technique was the survey that was applied to the owners or managers of hairdressing centres with code S9602.00; data were collected from the Internal Revenue Service (SRI) website. The results made it possible to identify the key success factors, financial and non-financial indicators with qualitative and quantitative features respectively, so that they become essential aspects to analyse and include in the strategic planning of the establishments, so that they can measure their performance, identify possible errors and take assertive measures that favour long-term performance and sustainability. On the other hand, results such as net working capital of $ 255, net profit of $ 4 573, current liquidity of $ 2,14, debt to assets ratio 46 %, ROA of 72% and ROE of 9 3%, in which, it is evident that it is a financial leverage and an excellent profit margin of 9,39 % on average, in addition, organizations should take into account the averages that were obtained throughout the research. Finally, the conclusions highlight that owners who wish to enter the market must take into account the barriers to entry such as: lack of experience, initial investment required, licenses and regulations to start up the specific economic activity.